Idiopathic Bilateral Extraocular Myositis in a Subject With Poorly Controlled Type 2 Diabetes Mellitus: Case Report - Tatsumi, Fuminori; Fushimi, Yoshiro; Sanada, Junpei; Shimoda, Masashi; Kohara, Kenji; Kimura, Tomohiko; Obata, Atsushi; Nakanishi, Shuhei; Mune, Tomoatsu; Kaku, Kohei; Kaneto, Hideaki (Frontiers in Medicine, 2021)
Background Extraocular myositis is characterized by acute onset of orbital pain, extraocular muscle swelling, absence of thyroid disease, and effectiveness of steroid therapy. While oculomotor nerve paralysis is often observed in subjects with diabetes mellitus, extraocular muscle paralysis is very rare among various diabetic mononeuropathies. In addition, while most diabetic mononeuropathies are observed as sporadic and/or unilateral neuropathy, bilateral mononeuropathy is also very rare. Case presentation A 58-year-old male visited our institution due to diplopia. He was diagnosed as type 2 diabetes mellitus about 10 years before and treated with oral diabetes agents. To examine the cause of his symptom, he was hospitalized in our institution. Slight ptosis was observed, and failure of adduction was observed in the right eye. Glycemic control was poor; HbA1c was 9.3%. Liver, renal and thyroid function were within normal range. Immunoglobulin (Ig) G was slightly high, but IgA, IgM and IgG4 were within normal range. Various antibodies were all negative. Angiotensin-converting enzyme level was within normal range. There were no abnormalities in brain magnetic resonance imaging (MRI). After admission, to alleviate glucose toxicity, we started insulin therapy. On day 17, adduction failure of the left eye was observed in addition to the right eye. Vertical movement was also impaired in both eyes. Slight ptosis was observed in both eyes, and the right eye was completely close. In orbital MRI, some high signal was detected in both extraocular muscles. We performed steroid pulse therapy twice. About 4 months later, ptosis and vertical and horizontal movements in both eyes were almost completely recovered. Finally, we diagnosed him as idiopathic bilateral extraocular myositis. Conclusions We should bear in mind the possibility of idiopathic bilateral extraocular myositis especially in subjects with poor glycemic control, although its incident rate is extremely rare.